MICROTEACHING SEBAGAI FASILITATOR PENGUASAAN KETERAMPILAN DASAR MENGAJAR OLEH CALON GURU - Ginting, Rahmadani Fitri; Ramadhani, Sabila (Sindoro: Cendikia Pendidikan, 2024)
This study aims to explore the role of microteaching as a facilitator for prospective teachers in mastering basic teaching skills essential for their future professionalism. The research employs a qualitative method involving observation and feedback analysis from peer reviews during microteaching sessions. The results indicate that while most prospective teachers effectively engage students at the beginning of lessons, challenges remain in concluding lessons and managing classroom dynamics. Furthermore, clarity in explanation and the ability to pose discussion-provoking questions emerged as key areas for improvement. These findings underscore the value of microteaching as a practical tool in teacher education programs.